PENGEMBANGAN PEMBELAJARAN SINYAL-SINYAL PERWASITAN FUTSAL BERBASIS MOBILE LEARNING - Amiq, Fahrial; Angga, Prayogi Dwina (Gelanggang Pendidikan Jasmani Indonesia, 2021)
The purpose of this study was to develop mobile learning-based futsal refereeing signals for students majoring in Physical Education, Health and Recreation. The research and development model used adopts Lee & Owens' research and development model. The stages of research development are as follows; 1) Assessment or analysis which is divided into two parts, needs assessment and front-end analysis, 2) Design (planning phase), 3) Development (product development), 4) Implementation (implementation). product development results), 5) Evaluation of the achievement of goals in development). The results of the development of mobile learning-based futsal refereeing products, which are realized in the form of an Android-based application, have the following characteristics: (1) Futsal-based refereeing signal products are developed based on answers to student needs for deepening of mobile learning materials for futsal refereeing signals; (2) Application of futsal refereeing signals based on mobile learning, has the aim of helping to improve understanding of the material of refereeing signals which is one of the materials in futsal courses; (3) Mobile learning-based futsal refereeing signals are realized in the form of applications that can be installed on smartphones; (4) Applications for futsal refereeing signals based on mobile learning contain signals that can be used by futsal referees as rules for futsal matches and their motion analysis.